2005
DOI: 10.1111/j.1460-9592.2005.01445.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of satisfaction level by parents and children following pediatric anesthesia

Abstract: We found that parents generally expressed a high degree of satisfaction which was good and correlated significantly with environmental comfort and postoperative observations performed by anesthetists and nursing staff. In the children, lack of fear at the moment of being anesthetized, and lack of anxiety on the day preceding surgery, were attributed to the serenity transmitted by the anesthetist and nurses. Significant anxiety resulted from the fear of an unpleasant impact with the operating room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 26 publications
1
47
0
2
Order By: Relevance
“…These measures conform to many of the 8 dimensions of patient-centered care as formulated by the Picker Institute Europe that are widely considered key determinants of quality; they include access, respect, coordination and integration of care, communication, physical comfort, emotional support, involvement of family and friends, and continuity of care [16]. Though satisfaction following pediatric anesthesia may not be similar to satisfaction following pediatric procedural sedation, the rate of satisfaction compares very favorably with such studies [8,11]. Iacobucci et al found a high overall parental satisfaction score with children undergoing general anesthesia, with a median score of 9 on a scale from 0–10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These measures conform to many of the 8 dimensions of patient-centered care as formulated by the Picker Institute Europe that are widely considered key determinants of quality; they include access, respect, coordination and integration of care, communication, physical comfort, emotional support, involvement of family and friends, and continuity of care [16]. Though satisfaction following pediatric anesthesia may not be similar to satisfaction following pediatric procedural sedation, the rate of satisfaction compares very favorably with such studies [8,11]. Iacobucci et al found a high overall parental satisfaction score with children undergoing general anesthesia, with a median score of 9 on a scale from 0–10.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was based on a previously validated instrument, slightly modified to reflect satisfaction with pediatric “sedation” instead of pediatric “anesthesia” [8] [Appendix A]. The instrument was designed to investigate several areas: quality of communication, quality of environment, quality of care provided by the anesthesiologists and sedation nurses, parental opinion of the child’s recollection, and parental opinion of the overall experience.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, parents were allowed to stay in the room during intravenous access or induction. High parental anxiety leads to increased anxiety in children, prolonged recovery process, higher pain scores, increased use of narcotic analgesics, and extended hospitalization periods (17,18). However, as the parents included in this study were observed and identified to have the ability to control their emotions, they were allowed to stay with their children, and this may have had a role in achieving a high satisfaction level.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, families were encouraged to participate in the survey, and high participation rates could be attributed to completing a questionnaire (17,24). However, the 22-question survey developed within the scope of this study provided the opportunity to examine the satisfaction levels of the relatives in detail.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Similar surveys focusing on various aspects of patient care have been published earlier. [3][4][5][6][7][8][9][10] We hypothesized that low patient satisfaction would let us detect problems related to, and arising during, digestive endoscopy. The aim of our study was to assess the most important items of the process of care via patient satisfaction on one side and via the collection of objective data as the concrete counterpart of satisfaction on the other.…”
mentioning
confidence: 99%